2016
DOI: 10.1371/journal.pone.0168073
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Portable Monitoring in Diagnosing Significant Sleep Disordered Breathing in Hospitalized Patients

Abstract: BackgroundPolysomnograms are not always feasible when sleep disordered breathing (SDB) is suspected in hospitalized patients. Portable monitoring is a practical alternative; however, it has not been recommended in patients with comorbidities.ObjectiveWe evaluated the accuracy of portable monitoring in hospitalized patients suspected of having SDB.DesignProspective observational study.SettingLarge, public, urban, teaching hospital in the United States.ParticipantsHospitalized patients suspected of having SDB.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…As stated in the previous section, the presented sample analysis was carried out on the data from the paper [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in the previous section, the presented sample analysis was carried out on the data from the paper [28].…”
Section: Resultsmentioning
confidence: 99%
“…The input file should be an Excel spreadsheet with two columns comprising reference AHI values and values from a tested device. Before any file is uploaded, the tabs present the results of the analysis of the default data, coming from [28], a study assessing the agreement between the AHI parameters measured by portable monitor and by reference polysomnogram. The data are not well concordant, which facilitates presentation.…”
Section: Shiny Web Applicationmentioning
confidence: 99%
“…The available literature on inpatient sleep testing is limited but demonstrates consistency in results, with a high level of concordance seen between portable sleep testing used in the inpatient setting and subsequent outpatient polysomnography for the diagnosis of obstructive sleep apnea. [30][31][32][33] Previous studies have shown that inpatient sleep monitoring, using either high-resolution pulse oximetry 33,34 or portable sleep monitors, is technically feasible 21,30,35,36 with failure rates ranging between 2% and 19%. Findings from the current study are congruent with previous reports, demonstrating a technical failure rate of 3.5% for respiratory polygraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Executing simultaneous recordings of both types of studies is of considerable value, as it has been previously observed that a significant number of central respiratory events initially noted on inpatient portable monitoring subsequently abated on outpatient polysomnography performed at a later date. 31 Indeed, the uncertainty regarding the reliability of portable sleep monitoring in identifying central sleep apnea has been a limitation in its use. Previous studies have primarily reported agreement on obstructive sleep apnea as the samples had predominantly obstructive disordered breathing events, and agreement for central vs obstructive events was not reported.…”
Section: Discussionmentioning
confidence: 99%